Ionic‐liquid‐modified magnetic nanoparticles as a solid‐phase extraction adsorbent coupled with high‐performance liquid chromatography for the determination of linear alkylbenzene sulfonates in water samples. Issue 5 (27th January 2017) - Lu, Junyu; Ye, Fanggui; Huang, Xiuxiang; Wei, Lianqiang; Yao, Dongmei; Li, Shengying; Ouyang, Miao; Lai, Hongfang
Abstract : Novel ionic‐liquid‐functionalized Fe3 O4 magnetic nanoparticles were synthesized by the thiol‐ene click reaction. The prepared functionalized Fe3 O4 nanoparticles possessed multiple interactions, such as electrostatic, hydrophobic, and π–π interactions. The functionalized Fe3 O4 nanoparticles were characterized by using Fourier transform infrared spectroscopy, X‐ray diffraction, vibrating sample magnetometry, and transmission electron microscopy. Four kinds of linear alkylbenzene sulfonates, namely, sodium decylbenzenesulfonate, sodium undecylbenzene sulfonate, sodium dodecylbenzenesulfonate, and sodium tridecylbenzenesulfonate, were selected as model compounds to evaluate the applicability of adsorbents for extraction and subjected to high‐performance liquid chromatography analysis. In addition, the effects of various parameters, such as sorbent amount, pH value, ionic strength, sample volume, extraction time, and elution conditions on extraction efficiency were studied in detail. Under the optimum conditions, good linearities were attained, with correlation coefficients between 0.9912 and 0.9968. The proposed method exhibited limits of detection ranging from 0.061 to 0.099 μg/L for all the target analytes. The spiked recoveries of the target analytes in real water samples ranged from 86.3 to 107.5%, with relative standard deviations lower than 7.96%. The enrichment factors of the analytes ranged from 364 to 391, indicating that the obtained functionalized Fe3 O4 nanoparticles can effectively extract trace target analytes from environmental water samples.